Livro infantil educativo para prevenção de queimaduras em crianças - Pitol, Debora Nassif [UNIFESP] (2018)
INTRODUCTION: Burning in childhood is a severe public health care problem that mainly affects developing countries such as Brazil. It is responsible for most child hospitalizations for external causes in the country and it leaves physical and psychological sequelae that can last for a whole lifetime. Prevention through education is one of the most effective ways to decrease the occurrence of this problem, and it needs to be targeted at children and adults. Although there were countless manuals and publications aimed at the prevention of burns, it still wanted a child's book which could be didactically worked on. OBJECTIVE: To develop an educational children's book to prevent burns in children. METHODS: Development of a children's book on the prevention of burns in children through bibliographic review in the main electronic scientific databases, with content formulated after consultation with experts in the field, elaborated through written and illustrated narrative, with the creation of a main character, Gelante. RESULTS: the product of this Master`s Degree is the book Gelante Giant Heart, an educational book on the prevention of burns in children, it is available in bookstores and it teaches children and adults about the main dangerous situations of burning, as well as values such as friendship and the fraternity. The book is composed of playful plot associated with images that help in the understanding of the message transmitted, mainly for child audience. CONCLUSION: A children's book was developed to prevent burns in children.